A Feasibility Study of CFETR 1/8 Sector Vacuum Vessel Mock-Up. (3rd April 2019) - Lu, Kun; Qin, Shijun; Xu, Zhuang; Zhang, Yang; Shen, Guang; Liu, Zhihong; Liu, Chen; Wei, Jing; Liu, Sumei; Song, Yuntao; Wu, Jiefeng
Abstract: The vacuum vessel (VV), one of the important components for the Chinese Fusion Engineering Test Reactor (CFETR) superconducting magnet tokamak, can provide an ultrahigh vacuum and clean environment for plasma operation. The CFETR VV was preliminarily designed to be a torus with a D-shaped cross section, eight upper vertical ports, eight equatorial ports, and eight lower ports. In order to verify the design and key technologies to be used in the future, a 1/8 VV sector mock-up has been designed and fabricated at the Institute of Plasma Physics, Chinese Academy of Sciences (abbreviated ASIPP). In this paper, the mock-up is used to demonstrate thick austenitic stainless steel plate hot forming, welding, cutting, part segment assembly, and other technologies and developments. The design considerations and criteria of the 1/8 sector mock-up are discussed in detail. Based on these considerations, the main design parameters and characteristics of the 1/8 VV sector mock-up are described, including the inner shells, outer shells, and stiffening ribs between them and the straight line, arcs, and the tangential joint between them. Finally, the research and development of technologies for the mock-up manufacture that has been carried out at ASIPP is discussed.